Fishing season estimation for tuna troll line fishing fleet at Palabuhanratu Nusantara Fishing Port, Sukabumi, Indonesia - Annida, Shafira Bilqis; Baihaqi, Faqih (Journal Omni-Akuatika, 2024)
Indonesia covers over 15% of global tuna production. This has placed Indonesia as the top tuna-producing country in the world. Troll line is one of the fishing fleets that targets tuna as main catch, operates in many areas in Indonesia, including those bases at Palabuhanratu Nusantara Fishing Port in Sukabumi. Fishermen complained about uncertain changes of the fishing season in recent years. This causes fishermen unable to determine the right time for fishing. Some trolling fishermen suffer losses and even bankruptcy. This study tried to estimate fishing season for trolling fleets based on three main catch commodities: skipjack tuna, yellowfin tuna, and bigeye tuna. Data on catches and fishing trips are collected monthly from 2018 to 2022 from the Sukabumi Regency Central Capture Fisheries Statistics Agency. Data was processed using a catch-per-unit effort approach followed by a fishing season index analysis. Results show that the three main catch commodities have similar fishing season patterns. Peak fishing season is from the beginning of the east season in June to the middle of the second transition season in October. Productivity of the three commodities reached its lowest point in the lean season in January and February, in the middle and end of the west season.Keywords: catch composition, fishing season, productivity, tuna